2012
DOI: 10.1007/s00253-012-4446-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential uses of spent mushroom substrate and its associated lignocellulosic enzymes

Abstract: Mushroom industries generate a virtually in-exhaustible supply of a co-product called spent mushroom substrate (SMS). This is the unutilised substrate and the mushroom mycelium left after harvesting of mushrooms. As the mushroom industry is steadily growing, the volume of SMS generated annually is increasing. In recent years, the mushroom industry has faced challenges in storing and disposing the SMS. The obvious solution is to explore new applications of SMS. There has been considerable discussion recently ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
134
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(138 citation statements)
references
References 81 publications
1
134
1
2
Order By: Relevance
“…More than 30 million tons of mushrooms were produced in 2013, which resulted in an accumulation of a large amount of spent mushroom compost (SMC) production. Approximately 1 kg of mushrooms generates 5 kg of SMC (Lau et al 2003;Phan and Sabaratnam 2012). Therefore, the waste management of SMC is a major problem confronted by mushroom producers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 30 million tons of mushrooms were produced in 2013, which resulted in an accumulation of a large amount of spent mushroom compost (SMC) production. Approximately 1 kg of mushrooms generates 5 kg of SMC (Lau et al 2003;Phan and Sabaratnam 2012). Therefore, the waste management of SMC is a major problem confronted by mushroom producers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the waste management of SMC is a major problem confronted by mushroom producers. The disposal strategies of SMC include burning, spreading on land, burying, composting with animal manure, or landfilling (Singh et al 2003;Phan and Sabaratnam 2012). Recently, some studies used SMC as a raw material to produce value-added products such as biogas, bulk enzymes, and organic fertilizer by bioconversion and as animal feed supplements (Bisaria et al 1990;Soechtig and Grabbe 1995;Kumaran et al 1997;Lim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because some wood-rotting fungi (mushrooms) such as Maitake (Grifola frondosa) and Nameko (Pholiota nameko) specifically require wood material for mushroom formation, sawdust-based mushroom substrate is used for the cultivation of these mushrooms. During cultivation, sawdust-based spent mushroom substrate (SSMS), which consists of the residual substrate and mycelial remnants from mushroom cultivation, is abundantly produced and amounts to several times more than the mushroom products (Phan and Sabaratnam, 2012). Therefore, in recent years, efforts to effectively recycle SSMS have increased because of environmental and economic issues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated the potential of using SSMS, other material-based spent mushroom substrates, and wood materials as animal feed additives, focusing on ruminants such as sheep and calves (Phan and Sabaratnam, 2012). Few studies have dealt with monogastric animals (Britton, 1978;Song et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that about 2.5 kg of spent mushroom substrates (SMS) or fresh SMC (spent mushroom compost) are produced for each kilogram of mushroom. Therefore, SMS management has become a major problem faced by farmers in several countries (Phan & Sabaratnam, 2012). SMS is an organic substance which used for an alternative growing media for horticultural plants so that it is conserving natural resources such as peat (Medina, Paredes, Pérez-Murcia, Bustamante, & Moral, 2009).…”
Section: Introductionmentioning
confidence: 99%